2014
DOI: 10.1371/journal.pone.0087772
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restriction and Fasting Arrest B and T Cell Development and Increase Mature B and T Cell Numbers in Bone Marrow

Abstract: Dietary restriction (DR) delays ageing and extends life span. Both long- and short-term DR, as well as short-term fasting provide robust protection against many “neuronal and surgery related damaging phenomena” such as Parkinson’s disease and ischemia-reperfusion injury. The exact mechanism behind this phenomenon has not yet been elucidated. Its anti-inflammatory actions prompted us to thoroughly investigate the consequences of DR and fasting on B and T cell compartments in primary and secondary lymphoid organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
4
21
1
2
Order By: Relevance
“…This result is congruent with previous reports [18, 19] and one possible reason for B cell decrease is inhibition of B cell differentiation in the BM during fasting [18]. …”
Section: Discussionsupporting
confidence: 93%
“…This result is congruent with previous reports [18, 19] and one possible reason for B cell decrease is inhibition of B cell differentiation in the BM during fasting [18]. …”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the blockade at the DN stage observed in our AIF −/Y mice, with alterations in the DN1, DN2, and DN3 stages, cannot be detected in the Lck-Cre animals. Of note, the adjustment in the mitochondrial metabolism profoundly alters DN1to-DN4 thymocyte development [9,10]. Remarkably, in contrast to previous results on Hq and CD19-Cre AIF KO mouse models [26][27][28], our findings originally indicated that the loss of AIF undoubtedly affected B-cell and erythrocyte development.…”
Section: Discussioncontrasting
confidence: 90%
“…Concerning thymopoiesis, less is known about the OXPHOS implication in the differentiation of double negative (DN) progenitor cells. However, a fine-tuning between ROS and glycolytic activation appears important for DN1-to-DN4 transitions [9,10]. Apoptosis-inducing factor (AIF), a Janus mitochondrial protein that is encoded by the Aifm1 (Aif, Pdcd8) gene on the X-chromosome, has been implicated in maintaining mitochondrial electron transport chain (ETC) function [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mouse thymus T cells are derived from the bone marrow, [27] they migrate in different parts of the thymus gland to differentiate and mature, and are released into the blood for immune response. Most studies suggest that immature thymus T cells normally develop into T cell lymphoma continuously, when CD4-/CD8- T cells are differentiated into CD4+/CD8- T cells and CD4-/CD8+ T cells from CD4+/CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%